The Effect of Financial Distress, Leverage, and Firm Size on Earnings Management - Dimas Prawira Drajat; Nengzih Nengzih (Politeknik Siber Cerdika Internasional, 2025)
Earnings management is a common practice among companies to adjust financial reports to achieve specific objectives. Factors such as financial distress, leverage, and firm size are suspected to influence earnings management practices. This study aims to analyze the effect of financial distress, leverage, and firm size on earnings management in infrastructure companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This research uses secondary data in the form of annual reports, with a total sample of 78 companies. The analysis method employed is panel data regression to examine the relationship between independent variables and earnings management as the dependent variable. The results indicate that financial distress has no effect on earnings management, leverage has no effect on earnings management, and firm size also has no effect on earnings management. These findings imply that these factors are not the primary determinants of earnings management practices in Indonesian infrastructure companies, highlighting the need for further research by considering other more relevant variables.